Detection of a characteristic length in 2D orthotropic micropolar continuum - Damjan Jurković; Gordan Jelenić; Sara Grbčić Erdelj; Dragan Ribarić; Laura Grbac; Edita Papa Dukić; Nina Čeh (Zbornik Radova)
With the aim of obtaining several micropolar engineering parameters, a numerical and experimental analysis of an artificially generated orthotropic microstructure is performed. Young’s moduli and Poisson's ratios of the microstructure are determined using homogenisation by asymptotic analysis. Four-point bending experiments are performed on the aluminium beams with the described microstructure. The same experiments are also performed numerically. Using the previously derived analytical expression for the strains in a plane orthotropic micropolar continuum, one characteristic length is determined. This length corresponds to the characteristic bending length in the isotropic continuum and is one of the four characteristic lengths of the planar orthotropic continuum. Experimental and numerical values agree well, despite the slight scatter of the experimental results. The methodology presented here can be used for further determination of bending lengths.